(untitled) (Nigerian Journal of Technology, 2016)
Compressive strength test was carried out on the protein-based lightweight foamed concrete produced with cement partially replaced by rice husk ash to ascertain its strength characteristics. Standard concrete cubes of 150 x 150 x 150 mm were produced using ordinary Portland cement (OPC), fine aggregate, aqueous protein-based foaming agent and rice husk ash (RHA). The RHA was used to replace cement at 5 %, 10 %, 15 %, 20 %, 25 %, 30 %, 35%, 40 %, 45 % and 50 % by weight of cement. Control cubes with no cement replacement (0 %), were also produced and used as reference points for comparing the compressive strength of the lightweight foamed concrete at 28 days and 56 days respectively. The mix proportion of 1:1.5 was used as binder/fine aggregate proportions with the foam occupying 20 % of the volume of the concrete and the other constituents occupying the remaining 80 %. The compressive strengths of the lightweight foamed concrete at both 28 days and 56 days, increased for cement replacement levels of 5 – 30 % and gradually decreased for cement replacement levels of 35 – 50 % respectively for the mix proportion of 1:1.5 and for the water/binder ratio of 0.4. The minimum 28 days compressive strength for the mix proportion of 1:1.5 at cement replacement level of 30 % and water/binder ratio of 0.4 was 15.52 N/mm2 while that at 56 days was 18.51 N/mm2. The rice husk ash is a pozzolanic material with a capability of contributing up to 80 % and above to the compressive strength of lightweight foamed concrete, if the percentage replacement does not exceed 30 %. The mix proportion of 1:1.5 at water/binder ratio of 0.4 produces a structural lightweight concrete at 28 days. http://dx.doi.org/10.4314/njt.v35i4.2